Do Poison Pills Increase Firm Risk? - TURK, Thomas (Institutional Knowledge at Singapore Management University, 2008)
Management scholars have argued that an active takeover market discourages risk-taking by managers and that takeover defenses serve to counter the risk-reducing pressures of an active takeover market. This study employs the Black and Scholes Option Pricing Model to determine whether or not adoption of poison pill securities increases investor perceptions of firm risk. The results provide evidence that the Option-Implied Standard Deviations of common stock returns increase significantly on the poison pill adoption date, on average. Furthermore, the implied standard deviations remained significantly above pre-adoption levels for several days after the poison pill adoption, suggesting that the perceived increase in firm risk is permanent. These results suggest the poison pills may serve a more constructive role in the governance of publicly traded firms than is generally assumed.